Curvature-adaptive multi-jet polishing of freeform surfaces. Issue 1 (2018) - Cheung, Chi Fai; Wang, Chunjin; Ho, Lai Ting; Chen, Jiangbo
Abstract: This paper presents a curvature-adaptive multi-jet polishing (CAMJP) method that can achieve high efficiency and cater for adaptation of the variation of the material removal rate ( MRR ) to the curvature of freeform surfaces. CAMJP makes use of a purposely designed multi-jet nozzle incorporated with a pressure control system. The effect of surface curvature on the MRR is analysed by computational fluid dynamic modelling. The fluid pressure of each jet is controlled independently to vary the MRR according to the curvature of freeform surfaces. Experimental results show that CAMJP is effective in improving the accuracy of polishing freeform surfaces.